1997
DOI: 10.1212/wnl.49.3.701
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin type B: A double-blind, placebo-controlled, safety and efficacy study in cervical dystonia

Abstract: We enrolled and treated 122 patients with idiopathic cervical dystonia in a double-blind, placebo-controlled safety and efficacy study of botulinum toxin type B (BotB). Both A-responsive and A-resistant patients were enrolled. Patients received intramuscular injections of either BotB (2,500 U, 5,000 U, or 10,000 U) or placebo. The primary outcome measure of efficacy was the Toronto Western Spasmodic Torticollis Rating Scale (TWSTRS)-Total score at 4 weeks following study drug administration. Secondary measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
105
0
11

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 233 publications
(123 citation statements)
references
References 13 publications
7
105
0
11
Order By: Relevance
“…To date, the vast majority of commercial development of botulinum toxin for clinical use has been based on BTX-A. However, studies indicate that botulinum neurotoxin serotypes B (BTX-B) and F (BTX-F) may be useful for the treatment of cervical dystonia or blepharospasm [6,7,11], especially for patients with cervical dystonia that no longer respond to BTX-A [8,12]. Clinical studies have found that BTX-A is more potent (less total number of units administered per patient per session) than BTX-B [7,8,13] and has a longer duration of action than either BTX-B, as indicated by electromyography (EMG) results only [13], or BTX-F as indicated by clinical response [6,12,14].…”
Section: History and Mechanism Of Actionmentioning
confidence: 99%
“…To date, the vast majority of commercial development of botulinum toxin for clinical use has been based on BTX-A. However, studies indicate that botulinum neurotoxin serotypes B (BTX-B) and F (BTX-F) may be useful for the treatment of cervical dystonia or blepharospasm [6,7,11], especially for patients with cervical dystonia that no longer respond to BTX-A [8,12]. Clinical studies have found that BTX-A is more potent (less total number of units administered per patient per session) than BTX-B [7,8,13] and has a longer duration of action than either BTX-B, as indicated by electromyography (EMG) results only [13], or BTX-F as indicated by clinical response [6,12,14].…”
Section: History and Mechanism Of Actionmentioning
confidence: 99%
“…6,7,11 Thus, the AE data obtained in controlled studies with doses of 2500 and 5000 U may not be entirely applicable to clinical practice. As shown in Figure 1, an apparent increase in dosages was observed over time in the present study, although the numbers of patients at each injection were not the same, with only a few patients having received 6 or 7 injections.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the present results apply only to the population of patients who reported xerostomia following botulinum toxin type B treatment. In controlled trials, 6,7,11 the percentage of patients with cervical dystonia reporting xerostomia following treatment with botulinum toxin type B ranged from 24% to 44% versus 3% with placebo.…”
Section: Discussionmentioning
confidence: 99%
“…Four Class I studies enrolled subjects with previous response to BoNT. Three studies assessed safety and efficacy of BoNT-B, 10,11,14 and one assessed safety and efficacy of BoNT-A. 13 One of these studies randomized 109 subjects with CD to placebo, medium dose, or high dose of BoNT-B.…”
Section: Description Of the Analytical Processmentioning
confidence: 99%